KAJIAN ADAT LARUNGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUI HASIL TANGKAPAN IKAN NELAYAN DI DESA BENDAR KECAMATAN JUWANA KABUPATEN PATI - , EKA NUR JANNAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was conducted to determine the differences in fish catch by fishermen who participated on Larungan tradition (physical join and dues contribution) and who did not participate on Larungan (only on participate on dues contribution) and determine the influence of internal and external factors to the fishing communities of fish catch. Larungan is a traditional ceremony that has been performed by the fishermen as an expression of gratitude to God Almighty. The method used in this research was descriptive analytic method. Differences on fish catch by fishermen who participated and did not participate on Larungan were analyzed using the t test and the factors that affect the fish catch of fishermen were analyzed using multiple linear regression. The analysis result showed that there was no difference in fish catch by fishermen who participated and who did not participate on Larungan. Factors affecting fish catch by the fishermen include age, facility/equipment to catch fish, and the length of time for fish catching at the sea.